Peixe-zebra (Danio rerio) Transgênico para o gene bmal1a: efeitos no relógio molecular do músculo esquelético - Sousa, Jucilene Pereira de (2016)
Most organisms have circadian rhythms with a periodicity of 24-hour that are generated by an endogenous mechanism, the molecular clock, which has the ability to synchronize biological functions with environmental signals. This mechanism has fundamental importance in the homeostasis of the tissues that are under its influence. Among the genes of the molecular clock machinery, the clock and bmal are positive regulators of clock mechanism and they present sigmoid expression profile in the skeletal muscle in zebrafish (Danio rerio). CLOCK and BMAL participate on the activation of the myogenic regulatory factors (MRFs - myoD, myog, myf5 and myf6), which are important in the development and differentiation of muscle cells. Despite this knowledge, the physiological importance of circadian rhythm in skeletal muscle of fish is not known. Therefore, the objective of the present study was to produce a zebrafish transgenic lineage that expresses bmal1a constitutively in the skeletal muscle to investigate the role of the molecular clock in the muscle. The transfer rate of the transgene to offspring, effect of transgenesis in the survival and fish growth, and expression of the bmal1a, clock1a and MRFs were investigated. The founding transgenic population (F0) was obtained after microinjection, and positive larvae were observed as specimens which presented green fluorescent heart. F1 was obtained from natural crossings between F0 and NT fish. Likewise, F2 was obtained from F1. F2 transgenic and NT were used in this study. The transgenic lineage was successfully generated with 50% transmission from the transgene to the offspring following a Mendelian model. The analysis of gene expression was made by qPCR. The survival (41,4±0% F2 and 44,3±6% NT) and growth (3.7±0.1 cm F2 and 3.8±0.2 cm NT) of F2 were not statistically different from NT fish. Among the genes, clock1a and myog presented statistically significant differences between the lineages with circadian profile in NT fish, suggesting that myog may be a clock controlled genes. The other genes (bmal1a, myf5, myf6, and myoD) presented constitutive expression. In general, it can be verified that the constitutive expression of bmal1a did not present change in the expression of the molecular clock, not affecting the homeostasis of the skeletal muscle, survival and growth.